Implementation of 5S in the Automotive Laboratory - A Case Study - Iskandar, Ranu; Arifin, Zainal; Sofyan, Herminarto (KnE Social Sciences, 2020)
This research aims to identify the difficulties of 5S implementation in the Automotive Laboratory of Mechanical Engineering at UGM Vocational School. This research belongs to the type of case study. The techniques of data collection are interviewing, observation, and questionnaire. The techniques of data analysis are by data reducing for interview result and category scoring for questionnaire result. The difficulties of implementing 5S at Automotive Laboratory of Mechanical Engineering, Vocational School UGM are that 1) unused lab materials are not concise yet, 2) trainer kit and engine stand are not well-organized, 3) it necessary to add visual aids, especially K3, and 4) there is no long-term 5S habituation. Possible solutions to those problems are by 1) organizing unused materials in accordance with the needs and storing them in the warehouse for materials which has never been used for years, while the necessary materials are placed in the middle of the working area, 2) designing the placement of practicum material using color labeling on the floor, 3) adding more K3 posters in automotive laboratory, and 4) increasing the tendering grants and establishing harmonious communication between educational staffs and students. Keywords: Automotive Laboratory, Seiri, Seiton, Seiso, Seiketsu, and Shitsuke.